Pioneers - Burch, Tillie E. (Raton, New Mexico)
This is the text of a speech given by Mrs. Burch to an unknown organizations about pioneers. Mrs. Burch chose to bypass the more well known local families and focused on families who had lived in Raton since the beginning. Who they were, what they did, stories they told are here.
Articles written by local people
Master list item #: 3
File location is in the Raton File Cabinet
Keywords: Doggett, Joseph; Doggett, Sarah Gillespie; Dogget, Oris; Dogget, Charles; Valien, Laura; Johnson, Lige; Popejoy, Fred; Stockton, Tom; Brown, Ed; Brown, Dove; Killmury; Sever, Abe; Howe, James; Rathburn, Sam (Mr. & Mrs.); Shemp, Emy Lou; Wriggleworth, Hiram (Mr. & Mrs.); Schwachheim, Tom "the Dutch blacksmith"; Rival, Jose; Hixenbaugh, Pap; Hixenbaugh, Abe; Hixenbaugh, John; Hixenbaugh, Bruce; Hixenbaugh, Bill; Hixenbaugh, Ed; Hixenbaugh, Anna; Dillman, George goat herd, "Goat Hill"; McAuliffe, Tim; Mrs. Willoughby, nurse; Sever, Hazel; Leason, Marjorie; Smythe, Sadie; Gillespie, Cart; Gillespie, Jim; Gillespie, George; Gillespie, Fayett; Gillespie, William; Merrill, Laura; Johnson, Sadie; Sever, Pete; Hudson, Delia; Johnson, Walter; Tomlinson, Ethel; Rival, Jose; Bennet, Jennie; McKee, Laura; Walsh, Grace; Dohorty, Helen; Lodge, Bessie; Guampbell, Pearl; Guampbell, Curran; Clifton School House; Circle Dot Ranch; History -- Raton, New Mexico; Local History; Life and Customs; Johnson Park; Texas; Willow Springs; Raton; Johnson Mesa